EGFR mutation status in Middle Eastern patients with non-squamous non-small cell lung carcinoma: A single institution experience. Issue 6 (December 2015) - Naderi, Samah; Ghorra, Claude; Haddad, Fady; Kourie, Hampig Raphael; Rassy, Marc; El Karak, Fadi; Ghosn, Marwan; Abadjian, Gérard; Kattan, Joseph
Highlights: The prevalence of EGFR mutation is non-squamous NSCLC in Lebanon is 12%. The prevalence of EGFR mutation is similar in the Lebanese and Caucasian population. The prevalence of EGFR mutation is lower in Lebanon than in other Asian countries. Abstract: Background: Epidermal growth factor receptor (EGFR) represents an important molecular target in the treatment of lung adenocarcinomas; many anti-EGFR therapies are approved as first line and second-line treatment in patients having metastatic lung adenocarcinomas. The occurrence of this mutation varies in terms of race; it is around 10% in Caucasians and can reach 30% in Asians. Its prevalence in our Middle Eastern region is not well known. Methods: Patients diagnosed with non-squamous non-small cell lung carcinomas between March 2013 and March 2015 were included. This study was conducted at Hôtel-Dieu de France University Hospital, a tertiary medical center in Lebanon. EFGR mutations were analyzed using real time PCR technique on the Rotor-Gene Q using Scorpions and ARMS technologies. The following data was collected: the patients' characteristics (age, gender, smoking status, stage), the samples' characteristics (histology subtype, TTF-1 and Napsin A immunostainings, the site and the adequacy and the type of the sample), and the mutational EGFR status (presence and type of mutation). These variables were analyzed using SPSS 20. Results: 201 patients were included. The mean age was 65.2 years [31–87]; 40.2% were females. 78.1% of the included patients were smokers or ex-smokers. 12.9% of patients had a localized disease, 17.4% a locally advanced disease and 69.7% a metastatic disease. Adenocarcinoma was the main histologic subtype found in 90.5% of patients, followed by large cell carcinoma (3.5%), adenosquamous carcinoma (3.0%) and non-small cell carcinoma not otherwise specified (3.0%). 11.9% of patients had an EGFR mutation: 48% of them presented a deletion on exon 19, 40.0% a L858R mutation on exon 21, 4.0% a G719X mutation in exon 18, 4.0% an insertion in exon 20, and 4% a T790M mutation in exon 20. The presence of an EGFR mutation was significantly associated with the female gender (two-third) ( p < 0.05) and the non-smoking status (two-third) ( p < 0.05). Conclusions: The prevalence of EGFR mutation (11.9%) detected in our Lebanese population is similar to that observed in the Caucasian population. This mutation is also significantly more frequent in females and non-smokers.